Working with grep, sed, and awk - Campesato, Oswald (Mercury Learning and Information, 2023)
The goal of this book is to introduce readers to three powerful command line utilities that can be combined to create simple yet powerful shell scripts for performing a multitude of tasks. The code samples and scripts use the bash shell, and typically involve very small text files so that you can focus on understanding the features of grep, sed, and awk. In the simplest terms, grep (global regular expression print) will search input files in data for certain words or word patterns and print the lines that match it. sed is useful for changing or modifying data. Awk is a programming language also used for searching a data file for certain patterns, but can also perform certain tasks on the pattern matches it finds. Aimed at a reader relatively new to working in a bash environment, the book is comprehensive enough to be a good reference and teach a few new tricks to those who already have some experience with these command line utilities.
Keywords: Data science, data analytics, Linux, Unix, shell scripts; Technology & Engineering / Engineering (General); Command languages (Computer science)